OC-068 A systematic review and meta-analysis of clonidine in diarrhoea or intestinal transit: clonidine has an objective anti-diarrheal effect - Fragkos, KC; Zarate-Lopez, N (Gut, 2015)
Introduction Clonidine has been considered an alternative treatment (usually after other treatments have failed) for refractory diarrhoea. The evidence is scarce in the literature and not conclusive. The purpose of the present paper is to gather available evidence and provide a systematic and more complete answer with regards to the effectiveness of clonidine for diarrhoea irrespective of clinical background. Method We performed a systematic review of clonidine and its effect on diarrhoea or intestinal transit. Pubmed/Medline, Scopus, EMBASE, and Google Scholar were searched including key words of diarrhoea, bowel and clonidine. Twenty two papers were found describing the treatment of diarrhoea (15 trials and 7 case reports). The data were categorised into tables. Meta-analysis was performed on the 15 papers. Meta-analysis was performed with a random effects model of the standardised mean difference and heterogeneity was quantified with I-square and publication bias was assessed with Egger's test. All test were performed in Stata 12.0 and RevMan 5.3. Results The meta-analysis included 15 studies with total sample size 386 subjects (82 Males; sample size range 2-88, median sample size 13; mean age of subjects 40.3). Clonidine (median dose per day 300 mcg, usually divided into 2 or three doses orally or full dose transdermal) has been used for treatment of diarrhoea in irritable bowel syndrome, ileostomy diarrhoea, short bowel syndrome, diabetic diarrhoea, withdrawal associated diarrhoea, faecal inctoninence and cholera. Studies were also performed on healthy volunteers. Results indicate an impressive effect of clonidine on diarrhoea with a significant decrease of stool volume to intestinal transit or stool frequency (SMD = -1.78 [-2.46, -1.10]. There is however significant heterogeneity (I-square = 87%) and publication bias ash hown by the funnel plot and Egger's test (p = 0.05). Conclusion Clonidine is effective for treatment of diarrhoea and should be considered as an alternative when all other medications have failed. Disclosure of interest None Declared.